Natural Polyhydroxyalkanoates-An Overview of Bacterial Production Methods - Fukala, Ivo; Kučera, Igor (Molecules (Basel, Switzerland), 2024)
Polyhydroxyalkanoates (PHAs) are intracellular biopolymers that microorganisms use for energy and carbon storage. They are mechanically similar to petrochemical plastics when chemically extracted, but are completely biodegradable. While they have potential as a replacement for petrochemical plastics, their high production cost using traditional carbon sources remains a significant challenge. One potential solution is to modify heterotrophic PHA-producing strains to utilize alternative carbon sources. An alternative approach is to utilize methylotrophic or autotrophic strains. This article provides an overview of bacterial strains employed for PHA production, with a particular focus on those exhibiting the highest PHA content in dry cell mass. The strains are organized according to their carbon source utilization, encompassing autotrophy (utilizing CO2, CO) and methylotrophy (utilizing reduced single-carbon substrates) to heterotrophy (utilizing more traditional and alternative substrates).
Keywords: polyhydroxyalkanoáty; uhlík; Polyhydroxyalkanoates; heterotrophy; Bacteria; PHA; PHB; methylotrophy; autotrophy; Carbon